2020
DOI: 10.1016/j.foodres.2020.109486
|View full text |Cite
|
Sign up to set email alerts
|

In silico mapping of microbial communities and stress responses in a porcine slaughterhouse and pork products through its production chain, and the efficacy of HLE disinfectant

Abstract: H. (2020). In silico mapping of microbial communities and stress responses in a porcine slaughterhouse and pork products through its production chain, and the efficacy of HLE disinfectant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In this context, animals are considered the main reservoir of MDR bacteria promoting the spread in the environment, from slaughterhouse throughout the food chain and subsequently humans ( Sobsey et al, 2006 ). Previous studies performed by our group and others showed that the contamination sources in the slaughterhouse (animals, slaughtering and meat chain production processes) are greatly responsible for the increased risks to food safety and consumer health due to MDR bacteria ( Lavilla Lerma et al, 2013 , 2014a , 2014b ; Zhu et al, 2013 ; Campos Calero et al, 2018 , 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…In this context, animals are considered the main reservoir of MDR bacteria promoting the spread in the environment, from slaughterhouse throughout the food chain and subsequently humans ( Sobsey et al, 2006 ). Previous studies performed by our group and others showed that the contamination sources in the slaughterhouse (animals, slaughtering and meat chain production processes) are greatly responsible for the increased risks to food safety and consumer health due to MDR bacteria ( Lavilla Lerma et al, 2013 , 2014a , 2014b ; Zhu et al, 2013 ; Campos Calero et al, 2018 , 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…Based solely on these observational indicator counts, IS, in some situations, can impact the levels of organisms present and in some cases have an impact lasting 16 weeks or more. Most studies that examine contamination or the impact of IS/disinfection in pork processing facilities do not make note of indicator organisms ( Campos Calero et al, 2020 ; Zwirzitz et al, 2020 ; Cobo-Díaz et al, 2021 ; Sui et al, 2023 ). In areas such as hospitals, replacing plumbing to disrupt recurring outbreak of carbapenem-resistant Enterobacteriaceae (CRE) led to a decline in CRE in patients; however, the environment was found to be rapidly recolonized by CRE and patient infections with CRE returned ( Decraene et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…These variations may have been more related to the community of bacteria present as well as those being introduced rather than a response to the IS. Differing combinations of bacterial species have been shown to resist disinfection ( Kocot and Olszewska, 2020 ; Pang et al, 2020 ); and bacterial communities in a pork processing plant were described to be influenced by the incoming carcasses as well as changes in the hygienic practices of the processing plant ( Campos Calero et al, 2020 ; Sui et al, 2023 ). Zwirzitz et al (2020) tracked the likely source of bacteria in a pork processing plant to the carcasses.…”
Section: Resultsmentioning
confidence: 99%